2010
DOI: 10.1108/02656711011084819
|View full text |Cite
|
Sign up to set email alerts
|

A study of quality management practices in TQM and non‐TQM firms

Abstract: PurposeThe primary objective of this research is to explore whether total quality management (TQM) firms execute various quality management practices significantly differently from non‐TQM firms in the Association of South East Asian Nations (ASEAN) automotive supply chain. The study also aims to analyze differences between different tiers of this supply chain and to examine the relationship between the implementation of quality management systems and adoption of TQM.Design/methodology/approachA total of 165 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…This fits with observations of quality management system work in industrial production. [3][4][5][6][7] However, no such effects could be demonstrated for patients who underwent autologous HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fits with observations of quality management system work in industrial production. [3][4][5][6][7] However, no such effects could be demonstrated for patients who underwent autologous HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it presents a role model to assess the value of a quality management system which defines infrastructures, equipment, release of products or services, responsibilities, training of personnel, acceptable criteria for admission and discharge, and requires implementation of standard operating procedures and continuous improvement strategies as key elements. [3][4][5][6][7] In this context, "JACIE" (www.jacie.org) and its US equiva-©2014 Ferrata Storti Foundation. This is an open-access paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Elg and Hultman (2011), many organisations are reluctant to implement CSR because of the cost of such implementation. Another potential reason why companies may be failing to adopt these tools was highlighted by Punnakitikashem et al (2010) who found that some manufacturing companies in the automobile industry did not face sufficient enough pressure from their higher tier supply chain partners to implement quality management tools and techniques. Similarly, it has been suggested that many organisations will only adopt CSR if it is made a requirement by their customers (Tsoi 2009).…”
Section: Manufacturing Vs Service Organisationsmentioning
confidence: 99%
“…Available elaborates are mainly focused on the system recognition of the relations between the parts manufacturer and cars manufacturer [28], management of the quality of suppliers [17], costs of the quality of suppliers [24], methods and devices used for the management of the quality in the automotive industry [22], systems, standards conditioning of the implementation of quality management in the automotive industry [6], effectiveness of the quality management systems [19], management of supplies chains [7] or applications of the quality management systems by suppliers [1]. As it comes to the precise issue concerning the quality of parts, in the analysed elaborates, it covered the control at the production stage and directly after it [14], standardization of the quality tests including the reliability for the parts manufacturers [4], quality challenges and the outline of directions of quality improvement for parts manufacturers [20], quality of the parts in the context of the calling actions [8] or the issues connected with logistics and packaging of automotive parts [29].…”
Section: Analysis Of the State Of The Issuementioning
confidence: 99%